2014
DOI: 10.1097/bot.0b013e3182a6df0a
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Syndesmotic Screw Position

Abstract: This study showed that syndesmosis fixation at the level of 30-40 mm above the tibiotalar joint has advantages with regard to stress in screws in comparison with the other evaluated levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
0
36
0
1
Order By: Relevance
“…In 2014, Verim et al performed a study of nite elemental analysis [39]. The syndesmotic screw was placed at six different altitudes above the plafond.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Verim et al performed a study of nite elemental analysis [39]. The syndesmotic screw was placed at six different altitudes above the plafond.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that a screw placed 2.0 cm above the tibiotalar joint resulted in less syndesmotic widening than a screw placed 3.5 cm above the joint, 145 whereas another showed that fixation 3 to 4 cm above the joint may have biomechanical advantages. 146 Clinical evidence has not demonstrated significantly different radiographic or clinical outcomes in transsyndesmotic Acute and Chronic Injuries to the Syndesmosis or suprasyndesmotic fixation. 147 Screw placement more than 4.1 cm above the joint negatively influences patient outcomes, likely due to decreased stability at this level or by slight bending of the fibula on insertion, causing widening at the mortise.…”
Section: Implant Placementmentioning
confidence: 98%
“…The authors of one study reported less syndesmotic widening with a screw at 2 cm than was seen when the screw was 3.5 cm above the plafond 65 ; another demonstrated increased fixation strength and less widening with fixation at 5 cm compared with when it was 2 cm above the plafond 66 . Finite element models have shown that 3.5-mm and 4.5-mm screws experience the lowest stress between 30 and 40 mm above the plafond whereas the least widening occurs with placement at 20 to 30 mm above the plafond 67 .…”
Section: Screw Positionmentioning
confidence: 99%